Viral metagenomics for swine health - Feehan, Brandi (Kansas State University, 2022)
Viral metagenomic sequencing describes an unbiased technique to identify viruses present in a sample. The rise of metagenomics, through next generation sequencing (NGS) and bioinformatics, has aided disease epidemiology, diagnostics, and vaccine development for the swine industry. Metagenomic techniques originated from labor intensive functional screening which NGS overcame by significantly increase the data output. Although, with this increase of data, computational methods were needed to elucidate biological significance. Therefore, bioinformatics made NGS relevant for viral metagenomics targeting swine health. Viral metagenomics for the swine industry involves uncovering molecular characteristics to aid in the development of vaccines, diagnostics, and therapeutics. We utilized metagenomics to identify a novel mammalian orthorubulavirus 5 (PIV5) while attempting to isolate porcine rotavirus B (RVB). During cell passaging, the responsible technician fell ill with symptoms of a respiratory infection. On passage four, cells exhibited the cytopathic effect of syncytia formation and were sent for NGS which identified a human PIV5 strain, named Moskva. The resulting genome demonstrated an 87% nucleotide identity to a human PIV5 strain. The original cell culture and pig fecal samples were negative for Moskva by qRT-PCR. Moskva formed a distinct clade from other PIV5 strains in a whole genome based phylogenetic tree. Comparing the two major surface glycoproteins, fusion (F) and hemagglutinin-neuraminidase (HN), amongst human PIV5 strains, Moskva had 32 and 31 amino acid substitutions, respectively. The novel PIV5 strain proved that further research is needed to determine prevalence of PIV5 in different mammalian hosts and geographical locations; in addition, the effects of amino acid substitutions in the viral surface proteins F and HN of the Moskva strain, especially with relevance to human health, need to be determined. Viral metagenomics was further applied to investigate Betaarterivirus suid 2 (PRRSV-2), the causative agent of porcine reproductive and respiratory syndrome (PRRS). PRRSV-2 detection and genome assembly through NGS approaches indicated that current PRRSV-2 analytic methods for NGS were insufficient. Nearly half of the PRRSV-2 qRT-PCR positive samples were unsuccessfully assembled using NGS. Read classification detected a novel porcine virus, a lentivirus, which was found especially as a coinfecting agent with PRRSV-2. While PRRSV-2 glycoprotein 5 (GP5) has been used historically for phylogenetic analysis, five of the ten PRRSV-2 genes illustrated increased nucleotide diversity when compared to GP5, indicating that other PRRSV-2 genes could be suitable candidates to demonstrate PRRSV-2 diversity. Comparatively, both the whole genome and GP5 phylogenetic trees lacked clustering patterns relative to temporal or geographical distribution, which also indicated the need for the use of a different PRRSV-2 gene for phylogenetic analysis. The use of a representative gene for PRRSV-2 classification is crucial to more accurately comprehend PRRSV-2 diversity and its implications for PRRSV-2 evolution, distribution, and virulence.
Keywords: Swine; Bioinformatics; Metagenomics